Guía de principios heurísticos de diseño de interfaz para el tratamiento de niños con déficit de atención considerando la evocación de emociones positivas (2019)
Since one out of every four children in Colombia suffers from attention de˙cit disorder and it is the main cause of children attending the psychologist at present, it is necessary that from a technological perspective we try to contribute to this problem and try to facilitate the work of the therapists. It is then important to consider the need for therapists to have reliable mobile applications that support therapies in their patients’ homes; However, from the perspective of developers, this work is complicated by the fact that there are no design guides that provide guidelines on how to develop reliable applications that are functional, support therapy, and, at the same time, evoke positive emotions. The search for this type of guides obtains scarce results in most of the contexts and the resulting investigations do not contain more than 10 unstructured guidelines that do not go beyond being general recommendations. In the project carried out in the master’s cycle it was possible to verify that the use of a guidelines guide for the design of interfaces can be very useful to optimize the design time and avoid that when designing random decisions that negatively impact on the receptivity of the user who will use the application. The present research seeks to establish a set of heuristic principles (guidelines) for the design of therapeutic systems interfaces for attention deficit disorder in children considering principles of evocation of positive emotions. For this purpose, 4 activities were defined: first, to carry out systematic reviews to determine and formalize the current state of research on the subject. Second, to perform a characterization of the attention deficit by finding the determining elements that the interfaces that contribute to this type of disorder must have. Third, to establish the principles necessary for the design of a therapeutic interface for the treatment of Attention De cit in children, creating the EMOINAD guide. Finally, it is proposed to carry out an evaluation of the resulting guide from four perspectives..